The role of PhoP/PhoQ two component system in regulating stress adaptation in Cronobacter sakazakii. (December 2021) - Ma, Yan; Zhang, Yingying; Chen, Ke; Zhang, Lingzhu; Zhang, Yibei; Wang, Xin; Xia, Xiaodong
Abstract: Cronobacter sakazakii is an opportunistic foodborne bacterial pathogen that shows resistance to multiple stress conditions. The PhoP/PhoQ two component system is a key regulatory mechanism of stress response and virulence in various bacteria, but its role in C. sakazakii has not been thoroughly studied. In this study, we found the PhoP/PhoQ system in C. sakazakii ATCC BAA-894 enhanced bacterial growth in conditions with low Mg 2+, acid pH, and the presence of polymyxin B. Moreover, the Δ phoPQ strain significantly reduced survival following exposure to heat, high osmotic pressure, oxidative or bile salts compared with WT strain. Furthermore, the RNA-seq analysis indicated that 1029 genes were upregulated and 979 genes were downregulated in Δ phoPQ strain. The bacterial secretion system, flagella assembly, beta-Lactam resistance and two-component system pathways were significantly downregulated, while the ABC transporters and microbial metabolism in diverse environments pathways were upregulated. qRT-PCR analysis further confirmed that twelve genes associated with stress tolerance were positively regulated by the PhoP/PhoQ system. Therefore, these findings suggest that the PhoP/PhoQ system is an important regulatory mechanism for C. sakazakii to resist various environmental stress. Highlights: PhoP/PhoQ enhanced C. sakazakii growth under various conditions. PhoPQ mutant exhibited reduced tolerance to different environmental stress. RNA-seq analysis revealed potential regulons of PhoP/PhoQ in C. sakazakii.